Vegetable diseases: - Koike, Steven T. (Elsevier/Academic Press, 2007)
The book offers an introduction to vegetable crops, descriptions of the disease-causing agents, suggested strategies for identifying and diagnosing vegetable diseases, and generally principles in controlling them.